Malaysia’s tourism demand from selected countries: the ARDL approach to cointegration - Mohd Salleh, Norlida Hanim; Othman, Redzuan; Ramachandran, Sridar (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
This paper investigates the long-run and short-run relationships between tourist arrivals to Malaysia and tourism price in Malaysia, tourism prices at alternative destinations, traveling costs, incomes and exchange rates, using the bounds testing approach developed within the autoregressive distributed lag (ARDL) framework. The empirical results show that in the long run, tourism price in Malaysia, traveling costs, tourism prices at alternative destinations and incomes are the important determinants of Malaysia’s tourism demand from the selected countries namely Singapore, Japan, Hong Kong and Australia. The results also indicate that the 1997-98 East Asian economic crisis and the outbreak of Severe Acute Respiratory Syndrome – SARS significantly affected Malaysia’s tourism demand.